Communicating about expected course and re-consultation for respiratory tract infections in children: an exploratory study. - Butler, C; Rollnick, S; Kinnersley, P; Tapper-Jones, L; Houston, H (2004)
Acute respiratory tract infection is the commonest reason for children consulting, and about one-fifth re-consult for the same illness episode. Fifty-nine audiotape recordings from nine general practitioners (GPs) consulting with children with acute respiratory tract infections were examined. Prognosis was mentioned in only 22 consultations, with GPs predicting a brief course in 11, a possibly longer than expected course in six, and with predicted duration not made explicit in five. Carers were invited to re-consult if they were 'unhappy' with the child's condition in 11 consultations, and specific triggers to re-consult were provided in 15. A patient information leaflet was given out only once. Providing carers with an evidence-based account of the likely clinical course and communicating specific triggers to re-consult may help them manage more of these illness episodes without re-consulting.